Komi can't communicate. Volume 1 - Oda, Tomohito, 1991-; Werry, John (Translator) (Shōnen Sandē komikkusu., 2019)
"Socially anxious high school student Shoko Komi would love to make friends, but her shyness is interpreted as reserve, and the other students keep her at a distance. Only timid Tadano realizes the truth, and despite his own desire to blend in, he decides to help her achieve her goal of making 100 friends."--Provided by publisher.